Excellent Service with the 3A Concept (Attitude, Attention, Action) at LPPP State University of Malang - Kartika, Intan Dina; Hardika; Baskara, Dwi Soca (Jurnal Ilmiah Sumber Daya Manusia, 2024)
This research aims to obtain information about excellent service with the concept of Attitude, Attention, and Action carried out at the Malang State University Education and Learning Development Institute (LPPP UM) office. The research method used is descriptive qualitative. Data collection was carried out through interviews with educational staff, observation, and documentation. The data obtained were analyzed using the Miles & Huberman model. The results showed that excellent service carried out by academic staff at LPPP UM has implemented the 3A concept well. Excellent service provided with the idea of Attitude has three main things, namely a polite and physically harmonious appearance, serving with a positive and logical attitude, and serving with an attitude of respect. Excellent service with the concept of Attention also has three main things, understanding sincerely, respecting behavior, and devoting full attention to guests. Excellent service with the Action concept has five main things, including always noting what guests want, recording guest needs, confirming and summarizing guest needs, trying to realize guest wishes as expected, and thanking guests.